2007
DOI: 10.14356/kona.2007013
|View full text |Cite
|
Sign up to set email alerts
|

The Shape of Pulverized Bituminous Vitrinite Coal Particles

Abstract: The shape of pulverized bituminous coal particles (vitrinites)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A value of 0.43 was used as an intermediate ke for particles between tetrahedral and smooth shapes as done previously [42]. The aspect ratio for flakiness was assumed to be 1 based on 3-D measurements for pulverized bituminous coal dust [49] and the results of Timbrell [50]. Using Equation 2, the volume shape factor was 0.37 as defined by Hinds [41] and indicates that dev should be 11% smaller than dpa.…”
Section: Test Dust Measurements By Ccsemmentioning
confidence: 99%
“…A value of 0.43 was used as an intermediate ke for particles between tetrahedral and smooth shapes as done previously [42]. The aspect ratio for flakiness was assumed to be 1 based on 3-D measurements for pulverized bituminous coal dust [49] and the results of Timbrell [50]. Using Equation 2, the volume shape factor was 0.37 as defined by Hinds [41] and indicates that dev should be 11% smaller than dpa.…”
Section: Test Dust Measurements By Ccsemmentioning
confidence: 99%
“…Neither particle temperature, nor size change considerably during the exposure time t exp . By doing a simple heat transfer calculation [33], a characteristic heating time for coal particles can be defined as…”
Section: A Pyrometry Of Moving Objectsmentioning
confidence: 99%
“…For this reason, when quantifying uncertainty caused by shape irregularity, based on [33,43,44], we assumed an average sphericity value of 0.74. The distribution of F p→m was set up for Monte Carlo simulations by computing the already perturbed value that did not contain variation caused by asphericity and multiplying this value by a normally distributed random variable determined by the relative standard deviation obtained in the view factor simulations at the sphericity value of 0.74.…”
Section: B Uncertainty Quantificationmentioning
confidence: 99%
“…The shape distribution investigated above gives a value of 0.825 for isometric particles. However, the values reported in the literature are 0.78 [9] and 0.73 [10], and in [11] it is suggested that if no more accurate information is available, one should use = 0.7. The difference between the two values, 0.825 and 0.7, is probably to be found in irregularities in real particle surfaces as compared with the smooth surfaces of the geometric shapes.…”
Section: Isometric Particlesmentioning
confidence: 99%